2023
DOI: 10.1021/acs.energyfuels.3c01904
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Methyl Orange on the Wettability of Organic-Acid-Aged Sandstone Formations: Implications for CO2 Geo-storage

Fatemah Alhammad,
Mujahid Ali,
Nurudeen Yekeen
et al.

Abstract: Carbon capture and sequestration are feasible techniques for achieving net-zero carbon emissions. In this respect, the storage capacity and fluid flow dynamics during carbon geostorage are controlled by the wettability of the geo-storage rock. However, as a result of the presence of organic acid contamination in sandstone geo-storage formations, the rock may attain a CO 2 -wet state, which would significantly reduce the CO 2 storage capacity. While nanofluids and surfactants have been recently utilized as wett… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 8 publications
(3 citation statements)
references
References 70 publications
(127 reference statements)
0
3
0
Order By: Relevance
“…Surface wettability has attracted much attention because of its importance in a wide range of practical applications that are related to interfacial phenomena, including boiling and condensation, , evaporation, supercritical solvent extraction, printing and coating, , desalination, carbon geo-storage, and so on. Contact angle is one of the most common key parameters to characterize wetting behavior.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Surface wettability has attracted much attention because of its importance in a wide range of practical applications that are related to interfacial phenomena, including boiling and condensation, , evaporation, supercritical solvent extraction, printing and coating, , desalination, carbon geo-storage, and so on. Contact angle is one of the most common key parameters to characterize wetting behavior.…”
Section: Introductionmentioning
confidence: 99%
“…Given the importance of wetting and spreading behaviors of water in high-temperature and high-pressure applications, such as boiling heat transfer in nuclear reactors, spray cooling, and carbon geo-storage, the temperature dependence of the contact angles of water has been explored since the 1960s. , A recent review provided a state-of-the-art review on this topic by focusing on how temperature affects the wetting behavior of water on solid surfaces.…”
Section: Introductionmentioning
confidence: 99%
“…Recent studies have demonstrated the wettability alteration of organic-acid-contaminated rocks by using nanofluids, surfactants, and certain chemicals such as methyl orange for EOR and gas (CO 2 and H 2 ) geo-storage purposes. , The results have shown that these surface-active agents can favor chemical flooding and CO 2 injection for EOR and CO 2 geo-storage. ,, Mechanistically, the presence of surfactants, nanoparticles, and methyl orange in the base fluid has a robust effect on altering the hydrophobic rock surface into a water-wet state . Similarly, CO 2 flooding has also depicted improved oil recovery in many previous studies. , In addition, changes in the oil viscosity and reduction of the interfacial tension (IFT) have contributed to the success of EOR projects …”
Section: Introductionmentioning
confidence: 99%